Optimum Flash-Less Cold Forging Process For AUV Propeller Fabrication With FEM - Tandur, Kahleed Hussain M (2010)
The selection of the manufacturing process, flash-less cold forging die design and optimization of work-piece are the major issues to reduce the overall cost of the propeller. Substantial investigations have been carried out on this area, by many researchers using various tools and techniques. However, cold forging of complex geometries such as propeller hub and blade is still lacking. Moreover, volumetric analysis and optimization of work-piece have not been reported so far for complex geometries. In this thesis, the cold forging process has been adopted to produce the propeller hub and blade.